Cell biology: a laboratory handbook - Celis, Julio E. (Academic Pr., 2006)
Contents of Volume 1: -- Part A. Cell and Tissue Culture: Associated Techniques. -- Section 1. General Techniques. -- Section 2. Culture of Specific Cell Types: Stem Cells. -- Section 3. Culture of Specific Cell Types: Haemopoietic, Mesenchymal, and Epithelial. -- Section 4. Differentiation and Reprogramming of Somatic Cells. -- Section 5. Immortalisation. -- Section 6. Somatic Cell Hybrids. -- Section 7. Cell Separation Techniques. -- Section 8. Cell Cycle Analysis. -- Section 9. Cytotoxic and Cell Growth Assays. -- Section 10. Apoptosis. -- Section 11. Assays of Cell Transformation, Tumorigenesis, Invasion and Wound Healing. -- Section 12. Electrophysiological Methods. -- Section 13. Organ Cultures. -- Part B. Viruses. -- Section 14. Growth and Purification of Viruses. -- Part C. Antibodies. -- Section 15. Production and Purification of Antibodies. -- Part D. Immunocytochemistry. -- Section 16. Immunofluoresence. -- Part E. Appendix. -- Contents of Volume 2: -- Part A. Organelles and Cellular Structures. -- Section 1. Isolation: Plasma Membrane, Organelles, and Cellular Structures. -- Section 2. Vital Staining of Cells/Organelles. -- Section 3. Protein Purification. -- Part B. Assays. -- Section 4. Endocytic and Exocytic Pathways. -- Section 5. Membranes. -- Section 6. Mitochondria. -- Section 7. Nuclear Transport. -- Section 8. Chromatin Assembly. -- Section 9. Signal Transduction Assays. -- Section 10. Assays and Models of in Vitro and in Vitro Motility. -- Section 11. Mechanical Stress in Single Cells. -- Part C. Appendix. -- Contents of Volume 3. -- Part A. Imaging Techniques. -- Section 1. Light Microscopy. -- Section 2. Digital Video Microscopy. -- Section 3. Confocal Microscopy of Living Cells and Fixed Cells. -- Section 4. Fluorescent Microscopy of Living Cells. -- Section 5. Use of Fluorescent Dyes for Studies of Intracellular Physiological Parameters. -- Section 6. Digital Image Processing, Analysis, Storage, and Display. -- Part B. Electron Microscopy. -- Section 7. Specimen Preparation Techniques. -- Section 8. Cryotechniques. -- Section 9. Electron Microscopy Studies of the Cytoskeleton. -- Section 10. Immunoelectron Microscopy. -- Part C. Scanning Probe and Scanning Electron Microscopy. -- Section 11. Scanning Probe and Scanning Electron Microscopy. -- Part D. Microdissection. -- Section 12. Tissue and Chromosome Microdissection. -- Part E. Tissue Arrays. -- Section 13. Tissue Arrays. -- Part F. Cytogenetics and in Situ Hybridisation -- Section 14. Cytogenetics. -- Section 15. In Situ Hybridisation. -- Part G. Genomics. -- Section 16. Genomics. -- Part H. Transgenic, Knockouts, and Knockdown Methods. -- Section 17. Transgenic, Knockouts and knock-down methods. -- Contents of Volume 4. -- Part A. Transfer of Macromolecules. -- Section 1. Proteins. -- Section 2. Genes. -- Section 3. Somatic Cell Nuclear Transfer. -- Part B. Expression Systems. -- Section 4. Expression Systems. -- Part C. Gene Expression Profiling. -- Section 5. Differential Gene Expression. -- Part D. Proteins. -- Section 6. Protein Determination and Analysis. -- Section 7. Sample Fractionation for Proteomics. -- Section 8. gel Electrophoresis. -- Section 9. Detection of Proteins in Gels. -- Section 10. Gel Profiling of Posttranslationally Modified Proteins. -- Section 11. Protein/Protein and Protein/Small Molecule Interactions. -- Section 12. Functional Proteomics. -- Section 13. Protein/DNA Interactions. -- Section 14. Protein Degradation. -- Section 15. Mass Spectrometry: Protein Identification and Interactions. -- Part E. Appendix